Crystallization study of the (1-x)Sb2O3-(x)SbPO4 glass system - Nalin, M. [UNESP]; Poulain, M.; Ribeiro, S. J. L. [UNESP]; Messaddeq, Y. [UNESP] (Elsevier B.V. Sa, 2008)
Antimony-based glasses have potential applications for all optical switching devices as well as for photosensitive materials. In both applications, the presence of a nano-scale antimony phase, inside the glass matrix, may increase the non-linear properties what is the prerequisite for further development. In this sense, to understand and to control the crystallization process of the glasses is the challenge for researchers. In this work, a systematic investigation have been done in order to determine the better composition and the thermal conditions to crystallize nano-scale antimony phases inside the binary glass system (1 - x)Sb2O3-xSbPO(4) (With 10 <= x <= 70, in mol%). Class samples have been annealed at specific temperatures for 5 11 and the resulting crystallized materials have been characterized using X-ray diffraction. FTIR, Raman and P-31 MAS-NMIR spectroscopies. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Glass; Antimony; Crystallization